Comparison of α-Smooth Muscle Actin (α-SMA) and Collagen Type III Expression after Conjunctival Excision Between Platelet-Rich Fibrin (PRF) Membrane and Conjunctival Autograft Treatment: An Animal Model Experimental Study on Oryctolagus cuniculus: Doi: 10.36351/pjo.v40i2.1760 - Indri Wahyuni; Reni Prastyani; Agung Bhakti Wiratama; Ismi Zuhria; Thomas Valentinus Widiyatno (Pakistan Journal of Ophthalmology, 2024)
Purpose: To evaluate the impact of Platelet-Rich Fibrin (PRF) membrane and conjunctival autografts on α-Smooth Muscle Actin (α-SMA) and type III collagen expression following conjunctival excision in Oryctolagus cuniculus. Study Design: Experimental study with a randomized post-test only design. Place and Duration of Study: Airlangga University, Surabaya in November 2022. Methods: Twenty rabbit eyes were categorized into two groups: those sutured with PRF membrane and those sutured with conjunctival autografts after temporal conjunctival excision. The study assessed α-SMA and type III collagen expression through the Immunoreactive Score (IRS) method.Data analysis is conducted using appropriate statistical methods, such as the t-test or Mann-Whitney U test, to compare the expression of α-SMA and collagen type III between the two groups. Results: The data for each sample represented the average IRS value observed at 200x magnification. In the conjunctival autograft group, the mean IRS of α-SMA expression was 5.52 ± 0.84,